2021
DOI: 10.37983/ijdm.2021.3201
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of microstructure and mechanical properties of PMMA Matrix composites reinforced with residual YSZ from CAD/CAM Milling process

Abstract: Background: Reinforcement of dental acrylics with fillers has yielded positive results. Different proportions of fillers have been added to strengthen the dental acrylics, but no consensus has been reached. Aim: The purpose of this study was to investigate the effects of the addition of different concentrations of yttria-stabilized zirconium (YSZ) obtained from the residues generated from the CAD-CAM milling of YSZ on the microstructure and mechanical properties of poly-methyl-methacrylate (PMMA)-YSZ composite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 33 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…Moreover, if recycled zirconia is not suitable for producing dental prostheses, it can be utilized in other applications while maintaining its high value. For instance, owing to its good chemical resistance and thermal stability, recycled zirconia powder has been used as a reinforcing filler to improve the mechanical properties of PMMA [33].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, if recycled zirconia is not suitable for producing dental prostheses, it can be utilized in other applications while maintaining its high value. For instance, owing to its good chemical resistance and thermal stability, recycled zirconia powder has been used as a reinforcing filler to improve the mechanical properties of PMMA [33].…”
Section: Discussionmentioning
confidence: 99%
“…PMMA is commonly used in dentistry to make denture bases, but its low mechanical strength makes it prone to fractures [42][43][44]. Previous studies demonstrated that incorporating recycled zirconia powder into PMMA can increase its mechanical strength by enhancing the physical molecular interactions between the PMMA matrix and zirconia through hydrogen bonding and van der Waals forces [33,34,45]. The strength of PMMA may not necessarily increase in direct proportion to the quantity of zirconia powder added, as excessive filler can disrupt the continuity of the resin matrix, leading to a decrease in the strength of the reinforced PMMA [33,34].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations